Q: 2x - y - 4 = 0
3x + y - 9 = 0
What is the solution set of the given system?

A: our answer is: x = 137/41 or 3.34

scijoe21|Points 1965|

Question

Asked 7/23/2012 7:23:53 PM

Updated 9/13/2014 2:26:09 AM

1 Answer/Comment

Rating

0

The solution for 2x - y - 4 = 0 , 3x + y - 9 = 0 is x = 13/5, y = 6/5 .

Two equation add , we get 2x+3x = 13 , x = 13/5

Put x = 13/5 in 2x -y -4 =0

2*13/5 -y = 4

y = 26/5 - 20/5

y = 6/5 .

Two equation add , we get 2x+3x = 13 , x = 13/5

Put x = 13/5 in 2x -y -4 =0

2*13/5 -y = 4

y = 26/5 - 20/5

y = 6/5 .

Added 9/13/2014 2:26:09 AM

x - 2y = 3
5x + 3y = 2
The lines whose equations are shown intersect at which point?
(1, -1)
(-1, 1)
(0, 3/2) **Weegy:** 31/8 and 25/8 (More)

Question

Expert Answered

Updated 7/22/2012 4:47:45 PM

1 Answer/Comment

To find this answer you need to try to plug in the x and y values into the equations and see which one solves both equations.

First lets plug in the point (1,-1) into the first equation x - 2y = 3

1 - 2(-1) = 3

1+ 2 = 3 This works here lets try the other equation

5x + 3y = 2

5(1) + 3 (-1) = 2

5 - 3 = 2 This works as well so this is your answer

First lets plug in the point (1,-1) into the first equation x - 2y = 3

1 - 2(-1) = 3

1+ 2 = 3 This works here lets try the other equation

5x + 3y = 2

5(1) + 3 (-1) = 2

5 - 3 = 2 This works as well so this is your answer

Added 7/22/2012 4:47:47 PM

Solve the system algebraically.
2x+ y - 10 = 0
x - y - 4 = 0
What is the value of y?
1/3
2/3
14/3 **Weegy:** Adding both equations gives us 3x=14; Therefore x=14/3. Substituting this value to the second equation gives: (14/3)-y=4; Grouping similar terms: (14/3)-4=y; (14/3)-(12/3)=y;y Therefore is 2/3 (More)

Question

Expert Answered

Updated 7/22/2012 5:37:01 PM

1 Answer/Comment

2x+ y - 10 = 0 x - y - 4 = 0 What is the value of y? 1/3 2/3 14/3

To solve for y subtract the 2 equations

2x + y - 10 = 0

-x + y + 4 = 0

Answer is x + 2y - 6 = 0

get numbers on one side so x + 2y = 6

to solve for y we need it on a side by itself so we need to subtract x from both sides. When we do this we have 2y = -x + 6.

Now we divide both sides by 2 to isolate the y.

y = -x/2 + 3 This is the answer

To solve for y subtract the 2 equations

2x + y - 10 = 0

-x + y + 4 = 0

Answer is x + 2y - 6 = 0

get numbers on one side so x + 2y = 6

to solve for y we need it on a side by itself so we need to subtract x from both sides. When we do this we have 2y = -x + 6.

Now we divide both sides by 2 to isolate the y.

y = -x/2 + 3 This is the answer

Added 7/22/2012 5:37:29 PM

2x+ y - 10 = 0 x - y - 4 = 0 What is the value of y? 1/3 2/3 14/3

To solve for y subtract the 2 equations

2x + y - 10 = 0

-x + y + 4 = 0

Answer is x + 2y - 6 = 0

get numbers on one side so x + 2y = 6

to solve for y we need it on a side by itself so we need to subtract x from both sides. When we do this we have 2y = -x + 6.

Now we divide both sides by 2 to isolate the y.

y = -x/2 + 3 This is the answer

To solve for y subtract the 2 equations

2x + y - 10 = 0

-x + y + 4 = 0

Answer is x + 2y - 6 = 0

get numbers on one side so x + 2y = 6

to solve for y we need it on a side by itself so we need to subtract x from both sides. When we do this we have 2y = -x + 6.

Now we divide both sides by 2 to isolate the y.

y = -x/2 + 3 This is the answer

Added 7/22/2012 5:37:29 PM

Solve the system algebraically. Check your work.
5x + 2y = 10
3x + 2y = 6 **Weegy:** 5x+2y=10_3x+2y=6
Since 2y does not contain the variable to solve for, [ move it to the right-hand side of the equation by subtracting 2y from both sides.
5x=-2y+10_3x+2y=6
Divide each term in the equation by 5.
x=-(2(y-5))/(5)_3x+2y=6
Since the equation was solved for x, replace all occurrences of x in the other equations with the solution (-(2(y-5))/(5)).
x=-(2(y-5))/(5)_3(-(2(y-5))/(5))+2y=6
Multiply -2 by each term inside the parentheses.
x=((-2y+10))/(5)_3(-(2(y-5))/(5))+2y=6
Remove the parentheses around the expression -2y+10.
x=(-2y+10)/(5)_3(-(2(y-5))/(5))+2y=6
Divide each term in the numerator by the denominator.
x=-(2y)/(5)+(10)/(5)_3(-(2(y-5))/(5))+?
Simplify each expression in -(2y)/(5)+(10)/(5).
x=-(2y)/(5)+2_3(-(2(y-5))/(5))+2y=6
Multiply -2 by each term inside the parentheses.
x=-(2y)/(5)+2_3(((-2y+10))/(5))+2y=6
Remove the parentheses around the expression -2y+10.
x=-(2y)/(5)+2_3((-2y+10)/(5))+2y=6
Divide each term in the numerator by the denominator.
x=-(2y)/(5)+2_3(-(2y)/(5)+(10)/(5))+2y?
Simplify each expression in -(2y)/(5)+(10)/(5).
x=-(2y)/(5)+2_3(-(2y)/(5)+2)+2y=6
Multiply 3 by each term inside the parentheses.
x=-(2y)/(5)+2_(-(6y)/(5)+6)+2y=6
Reorder the polynomial -(6y)/(5)+6+2y alphabetically from left to right, starting with the highest order term.
x=-(2y)/(5)+2_-(6y)/(5)+2y+6=6
Find the LCD (least common denominator) of -(6y)/(5)+2y+0.
x=-(2y)/(5)+2_Least common denominator: 5
Multiply each term in the equation by 5 in order to remove all the denominators from the equation.
x=-(2y)/(5)+2_4y=0
Since the equation was solved for y, replace all occurrences of y in the other equations with the solution (0).
x=-(2y)/(5)+2_y=0
Since the equation was solved for y, replace all occurrences of y in the other equations with the solution (0).
x=-(2(0))/(5)+2_y=0
Multiply -2*0 to get 0 in the numerator.
x=(0)/(5)+2_y=0
Any expression with a factor of 0 in the numerator is equal to 0.
x=0+2_y=0
Remove the 0 from the ... (More)

Question

Expert Answered

Updated 7/22/2012 5:29:45 PM

1 Answer/Comment

5x + 2y = 10 3x + 2y = 6 I would subtract the two equations thus you would have

5x + 2y =10

-3x - 2y = -6

The 2y would cancel out so you have 2x =4 divide both by 2 and you get x = 2.

Choose an equation and plug in a 2 for x for the first one you get 5(2) + 2y = 10

10 + 2y = 10

y = 0

Now to check try both numbers in the second equation to see if we are correct

3x +2y = 6

3(2) + 2(0) = 6

6 + 0 = 6

6 = 6

Your answer is (2,0)

5x + 2y =10

-3x - 2y = -6

The 2y would cancel out so you have 2x =4 divide both by 2 and you get x = 2.

Choose an equation and plug in a 2 for x for the first one you get 5(2) + 2y = 10

10 + 2y = 10

y = 0

Now to check try both numbers in the second equation to see if we are correct

3x +2y = 6

3(2) + 2(0) = 6

6 + 0 = 6

6 = 6

Your answer is (2,0)

Added 7/22/2012 5:29:45 PM

Simplify (3x + 5) + (2x - 9) - (4x + 3). **Weegy:** (3x + 5) + (2x - 9) - (4x + 3) = x - 7. [smile] (More)

Question

Expert Answered

Updated 3/1/2014 5:52:16 AM

1 Answer/Comment

(3x+5)+(2x-9)-(4x-3)=x-7

3x +5+2x-9-4x-3=x-7

=x-7=x-7

collect the like terms.

x-x=-7+7

x=0.

3x +5+2x-9-4x-3=x-7

=x-7=x-7

collect the like terms.

x-x=-7+7

x=0.

Added 7/22/2012 6:23:14 PM

This answer has been flagged as incorrect.

find the sum of the given polynomials.
2mn + 4n^2 and 5m^2 - 7mn **Weegy:** 2mn + 4n2 + 5m2 - 7mn = (c)5m2- 5mn+ 4n2 (More)

Question

Expert Answered

Updated 7/22/2012 7:33:34 PM

3 Answers/Comments

Added 7/22/2012 7:04:37 PM

This answer has been flagged as incorrect.

Added 7/22/2012 7:10:47 PM

This answer has been flagged as incorrect.

Rated good by John@evang, Flagged by debnjerry

27,403,183 questions answered

There are no comments.